The Practice Of Teaching Reading In English At Uka And Adare Primary Schools In Halu Woreda: Grade Eight In Focus - Belay Wodajo (My University, 2017)
The main objective of this study was to investigate the practices of teaching English reading skills at primary level especially in grade eight. It was used to answer two research questions. These were: First, what techniques of teaching reading in English as a foreign language are used in the primary levels especially in grade eight? Second, what are the challenges that negatively affect the children’s development of English reading skills? To gather information for the study classroom observation, students’ questionnaire, and teachers’ interview were used. For the purpose of this study, simple random sampling techniques were used. Accordingly, 80 students, 2 sections and 8 English language teachers were selected for the study. The data were categorized and descriptively analyzed. As a result, the findings depicted that inappropriate reading techniques were used in the mentioned grade level. Teachers were observed using the traditional way of teaching reading which was dominated by reading aloud. There was no time given for silent reading. Techniques of reading such as pre- and post- reading were not used at all. The consequence of wrong reading practices used has resulted in the weak performances of the students in their reading ability. To that end, this research paper provides recommendation that could bring about a change in the practice of teaching and learning reading in the grade level studied so that current techniques and procedures of teaching reading could be employed
Grade Eight In Focus